Clinical Procedures in Veterinary Nursing - Aspinall, Victoria (Edinburgh : Butterworth-Heinemann, 2008)
This book describes many of the clinical procedures performed by veterinary nurses in practice. It will help students to develop the skills needed as part of their training and will be useful later as a quick reference guide for up-to-date information on clinical procedures.
Handling and restraint / Victoria Aspinall -- Measuring clinical parameters / Richard Aspinall -- Medical nursing procedures / Jo Masters -- Administration of fluid therapy / Carole Martin -- Provision of nutritional support / Carole Martin -- Anaesthetic procedures / Pip Millard -- Theatre practice / Pip Millard -- Surgical nursing procedures / Trish Scorer -- First aid procedures / Trish Scorer -- Diagnostic imaging / Suzanne Easton -- Diagnostic laboratory techniques / Jennifer Davis -- Treatment of exotic species / Rachel Mowbray -- Preparing for the veterinary nursing exams / Justine Dunstone and Sarah Cottingham.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Veterinary nursing; Animal Diseases -- nursing; Animal Diseases -- therapy; Veterinary Medicine -- methods